Slavnosti sněženek - Menzel, Jiří (Czech Republic, 1983)
Acclaimed Czech director Jiří Menzel has pulled off another successful collaboration with writer Bohumil Hrabal in this light, sometimes saucy farce about two warring hunting factions in a small village and how they end up in a rousing, comic showdown. The village community is made up of a broad spectrum of eccentrics, from the farmer who escorts his goats to pasture in an old Pontiac car, to the sign painters who put up their handiwork slogans in the most unlikely places; there is humor enough for everyone. Then one day three hunters from one faction chase after a boar they found in the woods, and the wounded animal runs into a schoolhouse for refuge. Since the schoolhouse is in neutral territory, it becomes the scene for a reckoning between the two hunting factions. The upshot is a wild time in the local pub -- with some unexpected consequences
Duration: 01:23:00
Keywords: Fiction films